قياس الكفاءة النسبية للأقسام الأكاديمية بكلية الاقتصاد والعلوم الإدارية جامعة بخت الرضا خلال العام الدراسي 2016-2018م باستخدامتحليل مغلف البيانات - انس قريب الله احمد ابراهيم (White Nile Journal for Studies and Research, 2019)
This study aims to measure the relative efficiency of the academic departments at the Faculty of Economics and Administrative Sciences of the University of Bakht Alruda the period (2018-2016. We used the models of Data Envelopment Analysis (DEA) i.e. Constant Returns to Scale (CCR), and Variable Returns to Scale (BCC), by the orientation (output). The number of enrolled students at the eighth semester was the main output, and two inputs, the number of credit hours, and the number of successful students. Results of BCC reveal that four departments have achieved full efficiency, namely the Accounting and Finance Business Administration, Econometrics and Social statistics, and Rural Development. Economic department is the only inefficient. The results of CCR indicate that there is one department that has achieved the full efficiency that isthe Rural Development Department. The study recommends studying the reasons for the low efficiency of the departments and working on removing them until they achieve full efficiency. To preserve the achievement of full efficiency, and tackle cause leading to inefficiency.. Keywords: DEA, efficiency, credit hours, successful student, enrolled student.